NILAI-NILAI PENDIDIKAN ANAK USIA DINI BERPRESFEKTIF GENDER MELALUI TRADISI LISAN MASYARAKAT MELAYU SIAK - Violeta Inayah Pama (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
Education should be done since early childhood for the senses as the main medium to absorb the information on humans develop gradually and methods used in presenting the information was different. For infants and children, for example, methods with emphasis on hearing and vision will be more suitable than the sensory forward. Early childhood education receive directly from their parents because the parents are the first to be beside him since birth until the age increases. Education from parents, especially the mother will be absorbed by infants directly by using the tool senses gradually. One of the traditions of the Malay community is putting the child by the mother with a song that has a rhythm and a string of words that contain the word of Allah, moral teachings and contains the message and mandate. The singing is spoken by the mother when changing consciousness of children that are useful for the formation of character to face adult life. The tradition is positive for putting the child with a religious chant is a form of teaching that is done informally by parents. That means putting the child to be part of the duties of a mother for Siak Malay society. In connection with this, this paper tries to do the content analisys against the oral tradition so that the role played by the Malay women Siak accordance with the concept of gender.